Price-level targeting and inflation expectations: Experimental evidence - Rober Amano; Jim Engle-Warnick; Malik Shukayev (Bank of Canada, 2011)
In this paper, we use an economics decision-making experiment to test a key assumption underpinning the efficacy of price-level targeting relative to inflation targeting for business cycle stabilization and mitigating the effects of the zero lower bound on nominal interest rates. In particular, we attempt to infer whether experimental participants understand the stationary nature of the price level under price-level targeting by observing their inflation forecasting behaviour in a laboratory setting. This is an important assumption since, without it, price-level targeting can lead to worse outcomes than inflation targeting. Our main result suggests that participants formulate inflation expectations consistent with the target-reverting nature of the price level but that they do not fully utilize it in their forecasts of future inflation.
Keywords: E32; E52; 330; Monetary policy framework